Analysis of Factors Influencing Interest in Becoming Early Childhood Education Teachers among PGPAUD Study Program Students - Setianingsih, Dewi; Tasu’ah, Neneng (Universitas Negeri Semarang, 2025)
Interest in becoming a PAUD teacher is a person's desire to become a PAUD teacher and has more attention to the PAUD teaching profession. This study aims to describe the factors that influence interest in becoming an early childhood teacher in PG ECD study program students. This study used a qualitative approach with a case study type of research. Data collection techniques in this study include interviews, questionnaires, and documentation. Data analysis techniques in this study used the Miles & Huberman analysis model. The results stated that there were 23 students who were interested in becoming PAUD teachers. In accordance with the results of the study, there are factors that influence interest in becoming an early childhood teacher, namely internal factors including feelings of pleasure, attention to education, and ideals. Meanwhile, external factors include working hours, suitability of majors, family environment, and teaching experience.